(untitled) (Rajshahi University Journal of Life & Earth and Agricultural Sciences, 2015)
The purpose of this study was to investigate the violent and aggressive attitudes for student activists, non-student activists and student non-activists of different educational institutions within the framework of socio-cultural background. The study has been developed under the theoretical interpretation of biological theory of aggression and violence, and social learning theory of aggression and violence. It uses a multidimensional co relational approach with a criterion group design. The study was conducted into two phases. In the first phase criterion groups of student activists, non student activists and student non activists were selected on the basis of an activism criteria questionnaire. To achieve the goal 360 respondents was equally taken from student activists, non-student activists and student non-activists. Each sample group was sub-divided into upper middle and lower middle SES background. The violent and aggressive attitudes composed of five dimensions such as political violence, social violence, institutional violence, administrative violence and sex violence in the violence - nonviolence continuum. The main objective of the present investigation was to make a comparative study of the pattern of the attitudes of student activists, non-student activists and student non-activists. In this Study it was hypothesized that student activists would score higher on the attitudinal variables of violent and aggressive attitudes as compared to non-student activists and student non-activists respectively. The data were analyzed to obtain Mean, SD & t-test to test hypothesis. The result revealed that student activists were found to possess higher score on the attitudinal variable of violent and aggressive attitudes as compared to non-student activists and student non-activists respectively.